Key determinants of Instagram usage among Malaysian public university students: an extended technology acceptance model - Tian, Yang; Syed Zainudin, Sharifah Sofiah; Mohd Jalis, Farhana Muslim; Chan, Tak Jie (Redfame Publishing, 2023)
This research seeks to investigate the influencing factors affecting students’ intention of Instagram usage in Universiti Putra Malaysia. Drawn on the theoretical framework of the Technology Acceptance Model (TAM), social influence and self-efficacy were additionally incorporated to extend the TAM. A total of 373 online questionnaires were distributed to the targeted respondents. The PLS-SEM was applied for data analysis and the outcome shows that behavioral intention was positively anticipated by perceived usefulness, perceived ease of use, and social influence, while behavioral intention significantly impacts actual use. Meanwhile, the moderating effect of self-efficacy was found insignificant. The current study brings about empirical evidence in terms of the predictors anticipating students’ intention to use Instagram as an interactive platform by extending the TAM model. The outcome of the paper can serve as guidance for service providers in improving Instagram in the future.